INTEGRASI ILMU LINGUISTIK DALAM WACANA POLITIK UNDANG-UNDANG OTONOMI KHUSUS PAPUA: PERSPEKTIF STUDI MORFOLOGI - Warami, Hugo (Fakultas Ilmu Budaya, Universitas Mulawarman, 2018)
This study is part of an effort to understand the true value of basic philosophy that is revealed behind the law is really very meaningful in finding the words and concepts to describe the meaning of a text of the law. The provision of a special autonomy space for Papua is seen as a new sign that becomes a beacon within nationalists from the threat of Papuan nationalist groups (separatists and federalists) who are constantly creating new signs in the social semiotics space in Papua. Language as the home of life, capable of echoing and symbolized as a form of resurrection that is ready to threaten the unitary state system. The purpose of this study is to uncover political discourse in the text of law number 21 on Special Autonomy of Papua laden with linguistic nuances (morphology) which is not only what is understood, but the understanding itself is essentially linguistic as well. The method used in this research refers to qualitative method with descriptive research type which serves to present a detailed picture about a particular situation, social background, relationship, class or certain characteristic in Papua Special Autonomy Law. The main data in this study is the writing data (main) which is derived from the text of the Special Autonomy Law of Papua. The qualitative data derived from the text of the law in the form of words, phrases, clauses and sentences that provide an overview of the integration of morphological studies can then be described and explored in their meaning according to their use in the text.